A water-soluble polymer fluorescent probe via RAFT polymerization for dynamic monitoring of cellular lipid droplet levels and zebrafish imaging. (15th August 2022) - Cui, Wei-Long; Wang, Mao-Hua; Yang, Yun-Hao; Qu, Jianbo; Zhang, Haitao; Zhu, Xiuzhong; Wang, Jian-Yong
Abstract : A coumarin derivative was chosen for co-polymerizing with terminal hydroxy polyethylene glycol to obtain a water-soluble probe P(Cou-PEG-LD) . The probe was successfully applied to discrimination of starved and normal cells and zebrafish bioimaging. Abstract : Herein, the coumarin derivative was chosen as the luminescent parent and co-polymerized with a low-toxicity, highly hydrophilic terminal hydroxy polyethylene glycol to obtain the water-soluble probe P(Cou-PEG-LD) . The probe P(Cou-PEG-LD) possessed improved biocompatibility, interference resistance and photostability. Moreover, the probe exhibited optimal targeting properties toward lipid droplets and was successfully applied for dynamic monitoring of lipid droplet levels in HeLa cells. Interestingly, the sensitive labeling of the intracellular lipid droplet content using the probe P(Cou-PEG-LD) enabled the differentiation of starved and normal cells. The probe had also been successfully applied to zebrafish bioimaging and such specific features represented the great potential of the probe for disease prediction and treatment monitoring.